Evaluation of dietary curcumin nanospheres as phytobiotics on growth performance, serum biochemistry, nutritional composition, meat quality, gastrointestinal health, and fecal condition of finishing pigs - Moniruzzaman, Mohammad; Kim, Dahye; Kim, Hyunsoo; Kim, Nayoung; Chin, Sungyeon; Karthikeyan, Adhimoolam; Han, Kyuhyuk; Min, Taesun (Frontiers in Veterinary Science, 2023)
Curcumin is a bioactive functional feeding stimulant that is widely used as an additive in cuisine and animal feeds. Owing to its hydrophobic nature and low bioavailability, the nanoformulation of curcumin has recently received special attention from researchers. In this study, we investigated the effects of curcumin nanospheres (CN) on the growth performance, serum biochemistry, meat quality, intestinal immunohistochemistry, fecal malodors and microbes in finishing pigs. A total of 90 crossbred pigs (Duroc × [Yorkshire × Landrace]) with an average initial body weight of 73.77 ± 0.08 kg were randomized into 3 dietary groups in triplicate pens (10 pigs in each pen): control (CON) without supplementation of CN and the pigs in the remaining two groups were supplemented with CN at 1.0 (CN1) and 2.0 (CN2) mL/kg diet for a 40-day long experiment. The results showed that pigs fed the higher CN supplemented diet (CN2) had significantly higher final weight (FW) and weight gain (WG) than those fed the CON diet, and no significant differences were observed in the feed conversion ratio (FCR) and average daily feed intake (ADFI) after 28 days. At the end of the experiment, pigs fed the CN supplemented diet showed no significant difference in WG, ADFI or FCR compared to those on the CON diet. Overall, at the termination of the 40-day feeding trial, dietary CN had a significant effect on FW and WG, except for ADFI and FCR, in finishing pigs. After 40 days of the feeding trial, serum biochemical parameters such as glutamic-pyruvic transaminase, glutamic-oxaloacetic transaminase, triglycerides, and total cholesterol levels were significantly decreased in pigs fed the CN supplemented diet. However, high density lipoprotein levels were significantly increased in pigs fed the CN diets. Protein and lipid contents, as well as yellowness and lightness of the neck and longissimus dorsi muscles were not significantly affected by CN supplementation; however, there was a tendency to increase the redness of the longissimus dorsi muscle in pigs fed the CN2 supplemented diet compared to the CON diet. Meat grading and carcass weight significantly increased in pigs fed a higher CN supplemented diet. Fecal Escherichia coli and ammonia gas were significantly depleted in pigs fed CN diets. Histomorphological parameters, such as villus height, crypt depth and goblet cells in the jejunum of the intestine were significantly increased in pigs fed CN diet. Immunohistochemical staining showed that pro-inflammatory cytokine like tumor necrosis factor-α expression was reduced in pigs fed CN supplemented diets compared to the CON diet; however, antibodies such as immunoglobulin A and tight junction proteins such as claudin 3 were highly expressed in the intestine of pigs fed the CN diets. Overall, the results demonstrate the potential of dietary curcumin nanospheres as a nanobiotechnology tool as well as an effective feed additive for improving the performance and health status of finishing pigs.